1990
DOI: 10.1111/j.1365-2923.1990.tb02653.x
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of substance abuse: evaluation of a course of computer-assisted instruction

Abstract: A computer-assisted, experiential course of instruction on early diagnosis of substance abuse was developed and compared to three existing substance abuse curricula for third-year medical students on family medicine clerkships. The experimental course, requiring 2 hours of teacher contact, consisted of three computer-assisted instruction modules, active discussion, role play, opportunities for applying new knowledge and clinical skills, and modelling of clinical interest by a family doctor. The three compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There are difficulties in comparing computerised programmes with conventional learning due to a large number of con‐founding factors 16 . However, many programmes have been evaluated and have been shown to improve knowledge 17–20 . This has also been our experience.…”
Section: Discussionmentioning
confidence: 96%
“…There are difficulties in comparing computerised programmes with conventional learning due to a large number of con‐founding factors 16 . However, many programmes have been evaluated and have been shown to improve knowledge 17–20 . This has also been our experience.…”
Section: Discussionmentioning
confidence: 96%
“…Of the six studies that compared types of instructional strategies, 2833 four showed the different interventions to be equally effective in improving short-term outcomes. 2831 In general, the literature showed the more effective modalities to be active and experiential, such as structured role-play with standardized patients who function as instructors.…”
Section: Discussionmentioning
confidence: 99%
“…This instructional strategy is easy to scale up to large numbers of learners, which increases its educational impact. 33 …”
Section: Discussionmentioning
confidence: 99%
“…Drawbacks to this teaching approach compared to traditional formats are that it may involve more preparation time, involve equipment malfunction, and create an impersonal atmosphere with students. Despite these possible concerns, researchers have studied simulations that teach clinical problem-solving skills (Chan, Parker, Lam, Mecaskey, & Malphurs, 1987), behavior therapy (Lambert, 1987;Lambert & Lenthall, 1988), classroom management skills (Murphy, Kauffman, & Strang, 1987), sexual abuse assessment (MacFadden, 1989), diagnosis of substance abuse (Brown & Carlson, 1990), and child assessment (Isaacs, Costenbader, Reading-Brown, & Goodman, 1992). Fletcher-Flinn and Gravatt (1995) performed a meta-analysis of 120 experimental studies investigating a variety of CAI (e.g., laboratory demonstration, simulations, drill and practice) used with preschool to university-level students.…”
mentioning
confidence: 99%